2021
DOI: 10.1021/acs.analchem.0c04944
|View full text |Cite
|
Sign up to set email alerts
|

PDMS Curing Inhibition on 3D-Printed Molds: Why? Also, How to Avoid It?

Abstract: Three-dimensional (3D)-printing techniques such as stereolithography (SLA) are currently gaining momentum for the production of miniaturized analytical devices and molds for soft lithography. However, most commercially available SLA resins inhibit polydimethylsiloxane (PDMS) curing, impeding reliable replication of the 3D-printed structures in this elastomeric material. Here, we report a systematic study, using 16 commercial resins, to identify a fast and straightforward treatment of 3D-printed structures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 31 publications
1
91
0
Order By: Relevance
“…It has been suggested that curing inhibition on SLA resin can result from vaporised acrylate monomers 38 , which are components of most resins, released into the PDMS during heating. We reasoned that either blocking the contact sites between acrylates and PDMS or reducing the release of acrylates from the resin during curing could be sufficient to allow efficient curing of PDMS on the moulds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that curing inhibition on SLA resin can result from vaporised acrylate monomers 38 , which are components of most resins, released into the PDMS during heating. We reasoned that either blocking the contact sites between acrylates and PDMS or reducing the release of acrylates from the resin during curing could be sufficient to allow efficient curing of PDMS on the moulds.…”
Section: Resultsmentioning
confidence: 99%
“…Washing of resin E and D was unsuccessful in most conditions, due to the amount of uncured resin adhering to the print from improper printing, and subsequent analysis of PDMS curing on these samples would bias the curing time, if curing can take place at all. It has been suggested that curing inhibition on SLA resin can result from vaporised acrylate monomers 38 , which are components of most resins, released into the PDMS during heating. We reasoned that either blocking the contact sites between acrylates and PDMS or reducing the release of acrylates from the resin during curing could be sufficient to allow efficient curing of PDMS on the moulds.…”
Section: Optimisation Of Pdms Curing On 3d Sla Printed Mouldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two masters were fabricated with Vero White photosensitive resin (Stratasys, Ltd., Eden Prairie, MN, USA) by means of a 3D printer (Objet30 by Stratasys ® , Stratasys, Ltd., Eden Prairie, MN, USA). After a thorough cleaning in water to remove the support material, they were kept in oven at 110 • C for 12 h, which is a fundamental step to allow the following PDMS polymerization [31]. A final wash in acetone (5 min in ultrasonic bath) completed the fabrication process of the two masters.…”
Section: Sensing Platform Fabrication 221 Microfluidicsmentioning
confidence: 99%
“…It could also further streamline the adoption of the technology because of its simplicity, much as occurred with 3D (bio) printing [11,12]. While very promising for prototyping microfluidic and OoC devices, the adoption of 3D printing technology by biomedical researchers is currently hampered by concerns of cytotoxicity, optical clarity, limited resolution, and impeded curing of PDMS [12][13][14][15][16]. Efforts have been made to simplify microfabrication using cleanroom-free methods and/or low-cost, transparent substrates.…”
Section: Introductionmentioning
confidence: 99%